A Case of Congenital Syphilis Presenting with Unusual Skin Eruptions. (25th March 2018) - Leung, Alexander K. C.; Leong, Kin Fon; Lam, Joseph M.
Abstract : Once believed to be a rare disease in developed countries, recent data suggest that there is a surge in incidence of congenital syphilis in many developed countries. Diagnosis of congenital syphilis can be difficult because more than two-thirds of affected infants are asymptomatic at birth, and signs of symptomatic infants may be nonspecific or subtle. On top of this, some affected infants may have atypical presentations. Familiarity with the diverse presentations is essential to diagnosis. We report a 2-week-old male infant with congenital syphilis whose cutaneous manifestations included diffuse, erythematous keratoderma with desquamation and fissures on his hands and feet, multiple linear scaly fissures at the angles of his mouth, and onychauxis of the fingernails and toenails To our knowledge, diffuse, erythematous keratoderma of the hands and feet and thick nails have not been reported previously in congenital syphilis.